Self-injury in Australia: a community survey - Martin, Graham; Swannell, Sarah V; Hazell, Philip L; Harrison, James E; Taylor, Anne W (Medical journal of Australia, 2010)
Objective: To understand self‐injury and its correlates in the Australian population. Design, participants and setting: Cross‐sectional survey, using computer‐assisted telephone interview, of a representative sample of 12 006 Australians from randomly selected households. Main outcome measures: Data on demographics, self‐injury, psychiatric morbidity, substance use, suicidality, disclosure and help‐seeking. Results: In the 4 weeks before the survey, 1.1% of the sample self‐injured. For females, self‐injury peaked in 15–24‐year‐olds; for males, it peaked in 10–19‐year‐olds. The youngest self‐injurers were nine boys and three girls in the 10–14‐year age group, and the oldest were one female and one male in the 75–84‐year age group. Mean age of onset was 17 years, but the oldest age of onset was 44 years for males and 60 years for females. No statistically significant differences existed between those who did and did not self‐injure on sex, socioeconomic status or Indigenous status. Most common self‐injury method was cutting; most common motivation was to manage emotions. Frequency of self‐injury during the 4‐week period ranged from 1 to 50 instances (mean, 7). Self‐injurers were significantly more psychologically distressed, and also more likely to use substances. Adults who self‐injured were more likely to have received a psychiatric diagnosis. Self‐injurers were more likely to have experienced recent suicidal ideation (OR, 11.56; 95% CI, 8.14–16.41), and have ever attempted suicide (OR, 8.51; 95% CI, 5.70–12.69). Most respondents told someone about their self‐injury but fewer than half sought help. Conclusion: The prevalence of self‐injury in Australia in the 4 weeks before the survey was substantial and self‐injury may begin at older ages than previously reported. Self‐injurers are more likely to have mental health problems and are at higher risk of suicidal thoughts and behaviour than non‐self‐injurers, and many self‐injurers do not seek help.